Gamification and its impact on learning fundamental physics: A meta-analysis - Mohd Nor Azmi, Ab Patar; Nur Asyikin, Ahmad Nazri; Rodziah, Nazlan; Zulmaryan, Embong; Shaharudin, Ahmad; Jamaluddin, Mahmud (Human Resource Management Academic Research Society (HRMARS), 2024)
The objective of this meta-analysis is to methodically evaluate the efficacy of gamification in enhancing students' understanding of fundamental principles in the field of physics. Through an extensive exploration of scholarly databases, a significant body of research on the implementation of gamification in the context of physics education was discovered. This rigorous process led to a final sample of physics gamification studies that were included in the meta-analysis. The effect sizes were computed for each individual study and subsequently combined using meta-analytic methods to assess the overall influence of gamification on the results of physics learning. The meta-analysis reveals a statistically significant positive effect size (ES = 25.32, 95% CI: 1.75 to 48.89) indicating that gamification has a beneficial impact on students' understanding of fundamental physics concepts. Subgroup analyses further explore the moderating factors, such as the type of games employed and duration of intervention, shedding light on the specific conditions under which gamification is most effective. This meta-analysis shows a significant impact on the student's performance in the event gamification elements are introduced in the learning environment (P = 0.04). The present meta-analysis offers empirical data supporting the positive influence of the subject under investigation, and proposes potential directions for future research and the development of instructional design.